Human Resource Management in the Time of Covid-19 Pandemic: Trends and Challenges (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2021)
The contemporary pandemic of COVID-19 virus is a challenge for each organization in the world. Consequences are wide, and most of them are related to the labor force. Many countries reported a decline in the number of employees as a result of the economic downturn in 2020. Also, organizations all around the world are experiencing other problems with employees like higher level of fear and accompanied stress on workplace, lower employees' productivity, problems in teamwork because of remote working, personal physiological problems of employees due to social distancing, unprepared management teams for this kind of crisis, etc. During the crisis, organizations needed to adapt to the new normal in terms of implementing remote work for greater number of employees, reductions in working hours and even positions, reduction in training and development and compensation budgets, recruitment and career progress freeze, etc. A very sensitive process in this sense is human resource management (HRM), which now has to be re-invented in order to make an adequate response to new issues and challenges. It is important to investigate challenges that are arising in the HRM practice, and new trends that will be important for the future. Since the business is in the recovery phase, but still very harmful, HRM needs to be prepared for the new normal state and in that sense, it is important to be familiar with all potential threats and challenges and to investigate possibilities for overcoming the same. In the previous time, HRM has moved from administrative agent to strategic business partner. Now, it is very important to realize potentials that HRM as a business process has in terms of overcoming the problems that the pandemic brought to business and to investigate the necessity of moving HRM to the new level. The aim of the paper is to present the results of a questionnaire-based research from Hungary of the effects of COVID -19 to HRM practice. The results are very useful for HR managers from other countries from the Central and Eastern European region, to be prepared for this pandemic period and for the post Covid-19 times, too.